Майя Туровская: кино, культура и дух времени. Главы из будущей книги - Vladimir Paperny (eSamizdat)
Vladimir Paperny's two chapters from a future book include memoirs of his collaboration with the late film critic, cultural historian and the coauthor of the internationally acclaimed documentary "Ordinary Fascism" (1965) Maya Turovskaya (1924-2019). It also includes a transcript of his dialog with Turovskaya on the similarities between Soviet and American films of 1930s-1940s.